SEROPREVALENSI ANTIBODI IgGToxoplasma gondii PADA IBU DI RANGKAH 6 SURABAYA - Dwi Krihariyani Krihariyani; Evy Diah Woelansari; Entuy Kurniawan Kurniawan (Jurnal Ilmu dan Teknologi Kesehatan, 2015)
Toxoplasmosis is zoonotic diseases caused Toxoplasma gondii and can infected women. Risk factor Toxoplasmosis infection in women are habits of washing hand after contact wih animal. Thepurpose of the study was to research seroprevalence antibody IgG Toxoplasma gondii among women in Rangkah 6 Surabaya. This research is observational purposive sampling study.Total sample amount 45 sample from women and analyzed antibody IgG Toxoplasma gondii using ELISA technique. The result showed 57,5% (26/40) seropositive antibody IgG Toxoplasma gondii whereas42,5% (14/40) seronegative antibody IgG Toxoplasma gondii. Seropositive 6 of 26 women (23,1%) is pregnant women. Seronegative IgG T.gondii 5 from 14 (35,7%) is pregnant women.These research with Chi-Square test was level value p=0.976that meansno significantrelations between antibody IgG Toxoplasma gondii with habits of washing hand.The prevalence of Toxoplasma gondii antibody among women is high in Rangkah 6 Surabaya. these research will be neededAppropriated to screen women before and during pregnancy, should be dealt in order to minimize of this infection.